Association of Liver Stiffness with Hepatic Expression of Pharmacokinetically Important Genes in Alcoholic Liver Disease. (24th July 2012) - Theile, Dirk; Haefeli, Walter Emil; Seitz, Helmut Karl; Millonig, Gunda; Weiss, Johanna; Mueller, Sebastian
Abstract : Background: Enhanced drug elimination in alcoholics remains largely indefinable. In contrast, the reduced elimination of drugs in patients with advanced alcoholic liver disease (ALD) is normally owing to hepatic end‐stage disease such as cirrhosis. We here study the mRNA expression of various hepatic drug metabolizing enzymes and transporters in association with liver stiffness (LS) being a novel noninvasive parameter for the assessment of cirrhosis to unravel the dynamic relationship between ALD and determinants of pharmacokinetics such as drug metabolizing enzymes and transporters. Methods: We quantified mRNA expression levels of various cytochrome P‐450 isoenzymes (CYPs) and drug transporters in 26 liver specimens of chronic alcoholics and 5 controls by quantitative polymerase chain reaction. In addition, liver histology, clinical data, and LS evaluated by transient elastography (Fibroscan) were obtained. Results: Eighteen patients had a normal or moderate LS < 8 kPa (69.2%), while in the remaining 8 patients (30.7%) advanced F3 or F4 fibrosis could be established with an LS > 8 kPa. Overall, CYP3A4, CYP2E1, and solute carrier organic anion transporter 1B1 ( SLCO1B1 ) were negatively correlated with increasing LS. CYPs and drug transporters tended to be up‐regulated in alcoholics without advanced fibrosis (LS < 8.0 kPa) compared to healthy controls supporting data of boosted drug elimination in alcoholics without advanced ALD. However, in alcoholics with severely increased LS (>8 kPa), expression levels of CYP2E1, SLC22A2, and SLCO1B1 were significantly lower. Conclusions: In conclusion, CYPs and drug transporters seem to be induced in chronic alcoholics without irreversible liver damage but decline in case of manifest cirrhosis. Our study also suggests that noninvasive measurements of LS could be useful for pharmacokinetic predictions and individualized pharmacotherapy.